2015
DOI: 10.1039/c5ra09021k
|View full text |Cite
|
Sign up to set email alerts
|

Flexible carbon nanofiber sponges for highly efficient and recyclable oil absorption

Abstract: Carbon nanofiber sponges composed of three-dimensional networks have been prepared though chemical vapor deposition. Such sponges exhibit controllable bulk density, admirable mechanical flexibility and high oil absorption capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 45 publications
(95 reference statements)
1
25
0
Order By: Relevance
“…Over the past few years, carbon‐based oil sorbents have been extended from traditional activated charcoal, carbon microbelts,[12b] and graphite to recently developed nanostructured carbons such as carbon nanoparticles, carbon soot, carbon nanofibers (CNFs), graphene, and CNTs . By direct pyrolysis of certain types of biomass from nature, nanostructured carbon with hydrophobic properties can be easily obtained . Yu et al[15d] prepared an ultralight CNF aerogel through a one‐step pyrolysis of freeze‐dried bacterial cellulose (BC) pellicles ( Figure a).…”
Section: Surface Considerations For Oil Sorbentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past few years, carbon‐based oil sorbents have been extended from traditional activated charcoal, carbon microbelts,[12b] and graphite to recently developed nanostructured carbons such as carbon nanoparticles, carbon soot, carbon nanofibers (CNFs), graphene, and CNTs . By direct pyrolysis of certain types of biomass from nature, nanostructured carbon with hydrophobic properties can be easily obtained . Yu et al[15d] prepared an ultralight CNF aerogel through a one‐step pyrolysis of freeze‐dried bacterial cellulose (BC) pellicles ( Figure a).…”
Section: Surface Considerations For Oil Sorbentsmentioning
confidence: 99%
“…Pyrolyzed biomass has been regarded as an effective way to produce low‐cost carbon‐based oil sorbents . Wu et al reported a facile route to produce ultralight, flexible, and fire‐resistant carbon nanofiber (CNF) aerogels by pyrolyzing bacterial cellulose (BC) ( Figure a,g).…”
Section: Carbon‐based Oil Sorbentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only very few studies exist that present a template-free synthesis approach. [24][25][26] In this paper, we show a facile synthesis approach in which highly graphitic and highly flexible networks of three dimensionally interconnected, pyrolytic graphite-coated carbon nanotubes, named PyG networks in the following are grown that have a tailorable density and height with short production time.…”
Section: Introductionmentioning
confidence: 99%
“…By tuning catalyst amount, such CNF gels can exhibit a controllable bulk density of 0.02-0.14 g cm -3 and a high porosity of 92-98%. [117] In the C-CVD method, catalysts are critical to affect the formation and properties of CNF gels. Ni is one of the most The corresponding insets show high-magnification SEM images of both the graphene skeletons and CNF forest.…”
Section: Cvd Techniquementioning
confidence: 99%